Potentiel cicatrisant de Carthamus caeruleus chez les rats : Une évaluation de son effet régénérateur - BENADDA, IMENE; BENTAIFOURE, HADJ MUSTAPHA (My University, 2024)
Recently, much attention has been paid to medicinal plants for their proven therapeutic properties. Before starting the topical application, an identification of the plant Carthamus caeruleus.L was carried out. The study focused on determining the healing activity on the skin of rats and testing the skin irritation of open wounds of 2 cm² in diameter, then a cream preparation was applied to the spine. All products were applied topically in cream form. The parameters studied were the wound surfaces using the direct planimetry method as well as the speed of wound contraction. It was applied daily and measurements were taken every 4 days for 20 days. The results of the healing activity showed a healing observed after 20 days of treatment, an inhibition percentage of 98.02% for the cream based on Cartham and 96.35% for Madecassole and 68.76% for the group excipient and 68.20% for the control group. However, the effect showed statistically significant activity compared to the control. Eventually, the results obtained from the application of Carthamus caeruleus cream show that this extract accelerates healing. It could be that it exerts its activity accelerating hemostasis, by reducing the inflammatory phase, which promotes the acceleration of the epithelialization phase. The histopathology study carried out on the skin tissue of rats confirms the healing and regenerating effect of the cream made from the Carthamus caeruleus L plant.
Keywords: Carthamus caeruleus; Healing activity; Madecassole; Rats; Cream